Using the Participation Cube to Conduct Participation Analysis of Deve lopment Projects in Zambia and Uganda - Roberts, Tony; Howard, Jo (The Journal of Development Studies, 2025)
Cooke and Kothari argue that the seductive claims of participation oft en provide cover for shallow and tokenistic development practices that fail to address unequal power relationships. This paper provides a no vel mechanism that documents and enables a three-dimensional analysis of (a) who participates (b) at which project stages and (c) at what le vel of agency and power. No other mechanism was found in the literatur e for systematically tracing and analysing changes in power relationsh ip along all three dimensions. The application of this ‘participation tracing’ approach to two case study projects in Zambia and Uganda iden tified new opportunities to address power inequities thus moving in th e direction of what Hickey and Mohan refer to as transformative partic ipation. The method has only been applied retrospectively to date. Fur ther research is necessary applying the method proactively in project planning and during implementation as a form of participatory project assessment.
Keywords: Uganda; Zambia; analysis; cube; evaluation; participation; tracing